Quantifying drifting Fish Aggregating Device use by the world's largest tuna fishery. (21st June 2021) - Escalle, Lauriane; Hare, Steven R; Vidal, Tiffany; Brownjohn, Maurice; Hamer, Paul; Pilling, Graham
Abstract: Drifting Fish Aggregating Devices (dFADs) are a major fishing mode for tropical tuna purse seine fisheries worldwide. However, the extent of dFAD use remains poorly understood. We present novel approaches for estimating annual dFAD deployments and number of dFADs monitored by individual vessels, using empirical data and robust estimation procedures. We leveraged observer and logbook data, combined with new dFAD tracking data from the Western and Central Pacific Ocean (WCPO) purse seine fishery, the largest tuna fishery in the world, to evaluate trends in dFAD use across the entire WCPO between 2011 and 2019. Average estimates ranged between 20 000 and 40 000 deployments per year, depending on the methodology, with the total number of deployments appearing relatively stable over the last decade. The median number of active buoys monitored per vessel per day ranged from 45 to 75 depending on the year, well below the current management limit of 350. Our results contrast with other oceans, having fewer buoys monitored per vessel, a unique stable trend, but overall number of deployments two times higher than any other ocean. This study provides a basis for improved monitoring and management of dFAD use in the WCPO, with applicability for other regions.